Making global public policy work: A survey of international organization effectiveness. Issue 5 (8th August 2022) - Coen, David; Kreienkamp, Julia; Tokhi, Alexandros; Pegram, Tom
Abstract: Do international organizations (IOs) actually help address global problems? This question is of major concern for global governance scholars and policy makers, yet few existing studies review issues of effectiveness across a range of different issue areas. This paper generates comparative insights on IO performance across seven policy domains, namely climate change, development, finance, investment, migration, security, and trade. Based on a detailed expert survey, we consider how key IOs in these issue areas perform across three different measures of effectiveness: constitutive effectiveness, compliance, and goal achievement. We also investigate causal claims on effectiveness, exploring how IO institutional design – and in particular measures of authority – influence their ability to shape policy outcomes. Taking stock of the distribution of authority across issue areas and policy functions, we ask whether highly formalized, deeply constraining institutional arrangements have a consistently stronger impact on state behaviour or whether less formalized institutions with fewer discretionary powers can also contribute to the effective implementation of internationally coordinated policies. Finally, we identify key cross‐cutting challenges for global governance effectiveness, including political conflict and politicization, concerns related to legitimacy and representation, and growing problem complexity.